2011
DOI: 10.1007/s00125-011-2354-7
|View full text |Cite|
|
Sign up to set email alerts
|

Audit of acute Charcot’s disease in the UK: the CDUK study

Abstract: Aims/hypothesis We studied factors associated with the development and resolution of acute Charcot foot using a web-based observational study. centres. Of these, 36% of patients recalled an episode of relevant trauma in the preceding 6 months, while 12% had had surgery to the affected foot. In 101 (35%) cases, ulceration was present at registration and 20% of these had osteomyelitis. Non-removable off-loading devices were used at presentation in 35.4% of cases, with removable off-loading used in 50%. Data on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
3
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 15 publications
4
105
3
7
Order By: Relevance
“…The risk factors for CF are not yet well established (7,11,12). The identification, prevention, and early manipulation of risk factors might delay the appearance and progression of CF.…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors for CF are not yet well established (7,11,12). The identification, prevention, and early manipulation of risk factors might delay the appearance and progression of CF.…”
Section: Introductionmentioning
confidence: 99%
“…On theoretical grounds, BPPs may have clinical benefit, but the results of published studies are inconclusive. On balance, treatment with BPPs appears rather ineffective and even deleterious for the resolution time of the acute stage [22,33]; moreover, data on long-term outcomes are not available. There is, therefore, currently little evidence to support the use of BPPs as part of the routine management of patients with diabetes complicated by acute CNO.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, Pakarinen et al [23] reported that zoledronate did not reduce the duration of immobilisation, and may have increased it. Moreover, the recent audit of acute diabetic CNO in the UK based on a multicentre observational study [33] also showed that the use of BPP was associated with a longer time to resolution. These findings suggest that there is currently no evidence that adding a BPP to immobilisation and off-loading confers long-term benefits.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,19 It is now appreciated that this patient population is also vitamin D deficient with subsequent osteoporosis. Peripheral neuropathy, osteoporosis, and morbid obesity appear to be very important predisposing risk factors.…”
Section: Demographics and Pathophysiologymentioning
confidence: 99%